Analisis Perbandingan Undang-Undang Nomor 36 Tahun 2008 Tentang Pajak Penghasilan dengan Undang-Undang No 7 Tahun 2021 Tentang Harmonisasi Peraturan Perpajakan bagi Pajak Penghasilan (PPH Pasal 21) Orang Pribadi - Haviz Taufik (JURNAL RISET AKUNTANSI JAMBI, 2021)
This study examines changes to the layer of taxable income and the tax rate applied to the layer of taxable income for individual taxpayers from two laws, namely Law No. 7 of 2021 concerning Tax Harmonization and Law No. 36 of 2008 concerning Taxes. Income. From the test results, there are changes in the layers of taxable income and tax rates applied in Law No. 7 of 2021 concerning Tax Harmonization, 2) simulation results for taxes payable using Law No. 7 of 2021 concerning Tax Harmonization are smaller than Law No. 36 of 2008 concerning Income Tax; 3) The implementation of Law No. 7 of 2021 concerning Tax Harmonization can provide protection for low-income taxpayers by paying low taxes and at the same time provide opportunities for high-income taxpayers to contribute more to the source of state income derived from taxes.